ANALYSYS OF THE DEVELOPMENT OF DIGITAL TECHNOLOGY ON THE NEWSPAPER THE RADAR SAMPIT - Aquarini, Aquarini; Ilma, Miftahul (Yayasan Education and Social Center, 2025)
The development of digital technology is slowly changing people's habits in obtaining information. Information needs are now easily obtained quickly, can be accessed anytime and anywhere. This has an impact on the print media industry including newspapers.Newspapers or newspapers are one of the media that convey information about an event or current news. Newspapers are one of the oldest media for disseminating information. Inside they cover a variety of information ranging from crime, politics, editorials, to weather forecasts. Newspapers in print form have been in demand by the public since a long time ago. In addition to presenting the information that has been posted on the pages of newspapers, this media is also easy to obtain through mobile sellers or direct subscriptions. However, along with technological developments, newspapers have begun to be abandoned by their readers. People in the modern era have switched to digital news media in the form of a web (online) which can be accessed via a device or computer in real time, easily and quickly. Apart from that, online news is also considered more practical and free.The decline in the newspaper industry has already begun to be felt. National scale newspaper printing editorial office. They have changed their direction into digital media. This is because people's interest in reading news wants to be practical in the digitalization era. Not infrequently, many online media companies are starting to grow and develop ahead of print media. However, the existence of newspapers which have begun to fade on a national scale is not really felt in the print media industry on a local scale in Central Kalimantan. The local people of Central Kalimantan, especially East Kotawaringin Regency (Kotim), are still looking for newspapers as news media in the area. Even though online media is also starting to grow and develop in East Timor, the existence of print media outperforms online media which is also locally based.